PENGARUH PERCAYA DIRI DAN KEBERANIAN MENGAMBIL RESIKO TERHADAP KEBERHASILAN USAHA PADA USAHA TAMBAK UDANG DI KAMPUNG BUMI DIPASENA SEJAHTERA - Sima Ulya Nabila; Defrizal (Universitas Sarjanawiyata Tamansiswa, 2026)
This study aims to examine the effect of self-confidence and risk-taking courage on the business success of shrimp farming enterprises by emphasizing the psychological characteristics of entrepreneurs in fisheries business management. A quantitative research approach was employed, using primary data collected through structured questionnaires distributed to shrimp farming business operators. The collected data were analyzed using multiple linear regression to determine the influence of self-confidence and risk-taking courage on business success. The results indicate that both self-confidence and risktaking courage have a positive and significant effect on business success. Risk-taking courage plays a more dominant role in enhancing business performance, while self-confidence contributes to supporting long-term business sustainability. These findings highlight the importance of strengthening entrepreneurial psychological traits as a strategic effort to improve the success and sustainability of shrimp farming businesses.